Mysql Database Syncronization Using Restful Webservice Api PT. Minori - Felix Wuryo Handono; Sumarna; Hafis Nurdin; Fernando B Siahaan; Hary Sugiarto; Indra Chaidir (Jurnal Mantik, 2021)
PT. Minori is an apprentice delivery company to Japan located in Cikarang Bekasi. The apprentices to be sent to Japan must first follow the selection and education process. Even after arriving in Japan, the apprentices must take part in lessons too so they will not forget the educational material and move up to a higher level. The learning method during education is by accessing the Education server in LAN (Local Area Network) and accessing the cloud server during internship. The difference in location and network causes problems, the data that is on the local network server with the public network server, how to synchronize the data without changing the existing network infrastructure. Database synchronization in PT Minori is done by restful API from both servers to synchronize data.